"Wirsungectomy" for chronic pancreatitis - Yareshko, V. H.; Mikheiev, Yu. O.; Riazanov, D. Yu.; Shplenko, O.; Kanaki, A.; Ярешко, Володимир Григорович; Міхеєв, Юрій Олександрович; Рязанов, Дмитро Юрійович (My University, 2021)
Purpose: To evaluate a novel modification of the classic Partington-Rochelle procedure via comparing functional results between conventional surgery group and “wirsungectomy” group. Methods: A retrospective analysis of the case histories of patients with CP and an enlarged (≥4 mm) main pancreatic duct was carried out for the period from 2003 to 2009, which underwent surgical treatment of CP. The SF-36 and EORTC (QLQ) C30 questionnaires were used for assessment, visual analogue scale of pain. First group:wirsungectomy with lateral pancreatojejunostomy (PEA + WE) was performed - 5 patients; Second group: only lateral pancreatojejunostomy (PEA) was performed - 20 patients.Cross-tabulation analyses were performed to compare PEA and PEA + WE group as well as those groups in differenttimepoints using two-sided Student t-test. The significance level was set to p < 0.05. Results: Groups were compared in terms of VAS and the EORTC (QLQ) C30 questionnaire before and 2 years after surgery using Student's t-test for unrelated values: statistically significant differences between the groups according to VAS as before (p = 0.757) and after surgery (p = 0.696) were not obtained. There were no significant differences (p> 0.05) between the PEA and PEA + WE groups before and after surgery according to the EORTC (QLQ) C30 questionnaires, except for some items (p <0.05)Within the groups according to VAS and EORTC (QLQ) C30 (pain severity), in the PEA group (p = 0.000001, p = 0.000109) and in the PEA + WE group (p = 0.018, p = 0.017) after surgery, there was a statistically significant decrease in pain. Conclusion: Wirsungectomy is justified in patients with multiple calcifications in pancreatic ducts of the 2nd and 3rd order, with long-lasting CP and severe fibrosis of the pancreas, thus allow decompression of both the pancreatic parenchyma and the Wirsung duct. More cases needed for evidence-based comparison.
Keywords: Pancreatitis; Chronic; Pancreas; Abdominal Pain